ANALYSIS OF MARKETING MIX AT “WISATA BAHARI LAMONGAN” LAMONGAN, EAST JAVA - Mimit Primyastanto; Setiawan Setiawan; Heru Wiyoto (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
The growth of existing tourist in this time create emulation of tight business. To win an emulation, a company of including tourist have can give satisfaction to consumer, one of its way is optimal of variables had by company that is marketing mix. This research is executed at “ Wisata Bahari Lamongan” Lamongan, East Java. The purpose of this research are to analysis : (1) the influence of marketing mix by together to level satisfacation of tourism; (2) the influence of marketing mix by parsial to level satisfacation of tourism; (3) marketing mix variable most dominant to level satisfacation of tourism. The methods of this reseach is survai. Random sampling is technique to take the sampel. To determine the amount of sampel to be taken by Maxsimum Likelihood Estimation (MLE). Result of research indicate that F calculate (16.262) > F tables (2.09), this means satisfacation of tourism influenced by various factor by together that is: product which is offer have taste beauty and typically; reached price; strategic location; in accordance with reality of promotion; accuracy and comunicative employees; clean phisycal evidance and the axistence of adequate facility. Although separately, the variable give influence to satisfacation of tourism, can be seen that t calculate > t tables. From seven variable, there is one valuable variable of negative, that is price. Its meaning, if to be increasingly of price hence satisfacation of tourism will be decrease. Location variable is dominant variable of invluence satisfacation of tourism, becouse is have value of t calculate highestly. Keyword : marketing mix, ancient and tourism satisfacation